Physical activity as a pedagogical mediation strategy in the school classroom - Rodríguez Hernández, Mynor (2023)
Sedentary behavior and physical inactivity are considered a global pandemic that affects everyone equally. Generating secondary effects related to overweight, obesity, cardiovascular diseases, mental deterioration, among others. Costa Rica is not the exception, showing low levels of daily physical activity and a tendency to be overweight and obese, which compromises the health and quality of life of the population. The limited action from the physical education classroom, social influence and attachment to technology should be considered as barriers to maintain a physically active and healthy lifestyle in children. This study generates novel knowledge about the importance of developing academic programs from the regular classroom, which involve locomotor movement as a pedagogical strategy to reduce sedentary behavior and physical inactivity, as a possible solution to combat overweight and obesity in the Costa Rican child population. This research was developed following a qualitative approach, fifteen participants were recruited following a convenience sampling. Unstructured interview, non-participant observation and focus group were used as data collection strategies. Then, analyzed according to categorization, saturation and triangulation criteria. The inclusion of physical activity as a pedagogical mediation strategy for regular classroom teachers can improve physical, mental and social health, promote healthy growth and development, prevent risk factors for non-communicable diseases and help prevent overweight and obesity in children. It is essential that the regular teacher promotes pedagogical spaces that involve physical activity, according to the student's psychomotor development, through which the fundamental thematic axes for cognitive development would be addressed, contributing to the reduction of sedentary behavior, the risk of developing overweight and obesity and promoting significant learning.